Взаимодействие частиц шлама и износа в зоне контакта инструмента и детали при полировании неметаллических материалов - Филатов, Юрий Даниилович (НТУ "ХПІ", 2009)
It is established, that at interaction of not charged particles of deterioration and particles sludge they dissipate on corners 80–140° and of 50 nm move on circular trajectories in diameter. The charged particles of deterioration dissipate on corners 152–175° and of 150 nm move on channels in diameter.
Keywords: коэффициент объемного износа; распределения Пуассона; полировальный порошок; контактная зона